Agriculture and Nutrition in Bangladesh: Mapping Evidence to Pathways. (December 2015) - Yosef, Sivan; Jones, Andrew D.; Chakraborty, Barnali; Gillespie, Stuart
Background: Although much work has been done on the theoretical links between agriculture and nutrition, there is limited understanding of the evidence from observational and experimental research studies on the impacts of agriculture programs on nutrition outcomes. Objective: To assess the emphasis of the literature on different agriculture–nutrition pathways in Bangladesh. Methods: Twenty databases and Web sites were searched, yielding more than 2400 resources that were pared down through an iterative, eliminative process to 60 articles. These articles were then rated for quality and mapped to 1 of the 6 agriculture–nutrition pathways. Results: The body of evidence reveals gaps in knowledge in all of the pathways, but especially in the areas of agriculture as a source of livelihoods, and women's role as intermediaries between agriculture and good nutrition and health within their household. Conclusion: More research is needed on the links between agriculture and nutrition in country-specific settings, particularly as regards the role of women. Nutrition-related outcomes, such as dietary diversity and women's empowerment, need to be measured more explicitly when evaluating the impact of agricultural production systems and development initiatives.